Environmental oxygen tension regulates the energy metabolism and self-renewal of human embryonic stem cells. - Catherine E Forristal; David R Christensen; Fay E Chinnery; Raffaella Petruzzelli; Kate L Parry; Tilman Sanchez-Elsner; Franchesca D Houghton (PLoS ONE, 2013)
Energy metabolism is intrinsic to cell viability but surprisingly has been little studied in human embryonic stem cells (hESCs). The current study aims to investigate the effect of environmental O2 tension on carbohydrate utilisation of hESCs. Highly pluripotent hESCs cultured at 5% O2 consumed significantly more glucose, less pyruvate and produced more lactate compared to those maintained at 20% O2. Moreover, hESCs cultured at atmospheric O2 levels expressed significantly less OCT4, SOX2 and NANOG than those maintained at 5% O2. To determine whether this difference in metabolism was a reflection of the pluripotent state, hESCs were cultured at 5% O2 in the absence of FGF2 for 16 hours leading to a significant reduction in the expression of SOX2. In addition, these cells consumed less glucose and produced significantly less lactate compared to those cultured in the presence of FGF2. hESCs maintained at 5% O2 were found to consume significantly less O2 than those cultured in the absence of FGF2, or at 20% O2. GLUT1 expression correlated with glucose consumption and using siRNA and chromatin immunoprecipitation was found to be directly regulated by hypoxia inducible factor (HIF)-2α at 5% O2. In conclusion, highly pluripotent cells associated with hypoxic culture consume low levels of O2, high levels of glucose and produce large amounts of lactate, while at atmospheric conditions glucose consumption and lactate production are reduced and there is an increase in oxidative metabolism. These data suggest that environmental O2 regulates energy metabolism and is intrinsic to the self-renewal of hESCs.